Ultrasonographic study on the arterial variations of the arm and forearm in Malaysian adults - Aung, Htar Htar; Lwin, San San; Sa'at@Yusof, Azlin; Saharudin, Shahida (2012)
Introduction: The information and incidence of arterial variations have been implicated in different clinical situations. In Malaysia no study on the variants has been done in vivo. Methodology: 400 subjects (staff and students of IIUM) were examined with Logiq P5 General Electric Ultrasound machine using 12L- RS linear probe. Data analysis was carried out with SPSS 19. Results: The variants were found in 11% of the subjects (6.1% of upper limbs). Out of 800 upper limbs, there were seven types of variants; (a) persistent median artery (PMA) (2.6%), (b) brachioradial artery (BRA) (1.7%), (c) superficial brachioulnar artery (SBUA) (1.2%), (d) double radial artery (DRA) (0.6%), (e) brachioulnar artery (BUA) (0.2%), (f) radial artery (RA) loop (0.1%), and (g) aberrant radial artery (0.1%). Variations found in the arm were the BRA, SBUA and BUA while in the forearm were PMA, DRA, RA loop, and aberrant RA. Among them four cases of PMA were associated with BRA, SBUA, BUA, and aberrant RA on the same side. One case of BRA was found together with DRA on the left side. Although the variations were more slightly common in females (6%) than males (5%), and on the right side (3.5%) than the left (2.6%), these differences were not statistically significant (p > 0.05). Conclusion: This study confirms that the arterial variations of the arm and forearm are not uncommon. The microsurgical techniques for reconstruction of upper extremity could be fulfilled by thorough knowledge of the structural variations between individuals in different population.